PENGARUH KONSENTRASI ETANOL TERHADAP RENDEMEN EKSTRAK DAUN JATI BELANDA (Guazuma ulmifolia) DAN DAUN SUKUN (Artocarpus altilis) - Falestin , Senny Listy Kartika; Efrilia, Mega; Chandra, Pra Panca Bayu; Loimalitna, Pricillya Maria; Sabrina, Alifa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Dutch teak leaves and breadfruit leaves are natural ingredients used medicine. The secondary metabolite content Dutch teak and breadfruit leaf extracts believed to play a role in providing medicinal properties natural ingredients. Extracting natural ingredients with ethanol solvent can affect the yield. The aim research was to determine effect of variations in solvent concentration on the yield of Dutch teak and breadfruit leaf extracts. This research includes determination, collection and preparation of simplicia, making simplicia, extracts and determining the extract yield. This study, 20 grams of Dutch teak and breadfruit leaf powder were extracted with different solvent concentrations, namely 70%, 90% and 95% ethanol using maceration method. Replication was carried out in each solvent 3 times. Analyzed using descriptive methods and processed with Statistical Product and Service Solutions (SPSS) 26 tool. The highest yield research results were obtained from 70% ethanol extract of Dutch teak leaves (Guazuma ulmifolia) with an average of 2.79% ± 0.21 and extract ethanol 90% breadfruit leaves (Artocarpus altilis) with an average of 10.33% ± 0.33. The results the two way anova test, obtained a sig = 0.000 < 0.05 so that there were significant differences between plant groups and ethanol concentration the extract yield results.